SERS-based ultrasensitive detection of organophosphorus nerve agents via substrate’s surface modification - Zhao, Qian; Liu, Guangqiang; Zhang, Hongwen; Zhou, Fei; Li, Yue; Cai, Weiping (Journal of hazardous materials, 2017)
A strategy is presented to achieve the SERS-based ultrasensitive detection of organic-phosphor nerve agent sarin (simulant) via surface modification of the Au SERS-substrate, demonstrating a linear double logarithmic relation between the Raman peak intensity and the simulant concentration in the range from 1ppb to 1000ppm. [Display omitted] •A strategy for SERS-based ultrasensitive detection of sarin-simulant is presented.•Surface-modified SERS substrate can preferentially capture the sarin-simulant agent.•Raman peak intensity shows a linear double logarithmic relation with simulant content.•Such linear relation arises from Freundlich adsorption of simulant on the substrate.•The limit of detection for sarin-simulant agent is down to about 1ppb. Highly efficient detection of the organicphosphor nerve agents such as sarin and soman, based on surface enhanced Raman scattering (SERS) effect, has been in challenge due to their weak adsorption property on coin metals. In this paper, a new strategy is presented to achieve the SERS-based ultrasensitive detection of sarin-simulated agent methanephosphonic acid (MPA) via the surface modification of SERS-substrates. The Au-coated Si nanocone array is surface-modified with 2-aminoethanethiol and used as SERS-substrate for detection of MPA. It has been shown that the modified substrate could preferentially capture MPA molecules in the solution with coupling agent and induce amidation reaction. The reaction products are still bound or anchor on the substrate’s surface. The MPA molecules can thus be detected by Raman spectral measurement of the solution-soaked SERS-substrate. The minimum detection level is down to ∼1ppb. The Raman peak intensity versus the MPA concentration is subject to a linear double logarithmic relation from ∼1ppb to ∼1000ppm, which is attributed to Freundlich adsorption of MPA on the surface-modified SERS substrate. This study provides a new way for the highly efficient SERS-based detection of the organophosphorus nerve agents and some other target molecules weakly interacted with metal substrates.